2013
DOI: 10.1021/la401522v
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Synthesis of Thermoplastic Polymer Nanocomposite Materials with High Inorganic Filling Fraction

Abstract: The governing parameters controlling the miscibility of particle additives within polymeric host media are analyzed for the particular case of silica particle fillers embedded within a poly(methyl methacrylate) (PMMA) matrix. For athermal polymer-graft modification of particles (corresponding to equal chemical composition of graft and matrix polymer), compatibility is found to be a sensitive function of the degree of polymerization of graft and host polymer chains as well as the particle radius. In agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 42 publications
3
69
0
Order By: Relevance
“…Inorganic fillers such as silica are attractive reinforcements that are able to significantly improve thermal, mechanical and also chemical properties of PLA-based biocomposites [4,5]. Its valuable physicochemical properties along with high surface are the reasons for its widespread use [22,23]. Silica exhibits also a great potential for surface functionalization in terms of physical and chemical features and therefore gains even more possible applications [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic fillers such as silica are attractive reinforcements that are able to significantly improve thermal, mechanical and also chemical properties of PLA-based biocomposites [4,5]. Its valuable physicochemical properties along with high surface are the reasons for its widespread use [22,23]. Silica exhibits also a great potential for surface functionalization in terms of physical and chemical features and therefore gains even more possible applications [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Bockstaller and coworkers (Ojha et al 2013) have recently demonstrated that the enhanced control of the chemical composition of polymer grafts that is afforded by SI-ATRP facilitates the synthesis of thermoplastic polymer nanocomposite materials with high inorganic filling fraction. In particular, it was found that favorable interactions between grafted polymer and matrix polymer (here, poly(styrene-racrylonitrile)/poly(methyl methacrylate)) facilitate thermodynamically stable and uniform particle dispersion with inorganic filling fractions exceeding 50 % by volume (the term "polymer-filled inorganics" was introduced to highlight the majority content inorganic).…”
Section: Discussionmentioning
confidence: 99%
“…A particularly well-known example is the modification of gold (and other heavy metal) nanocrystals with thiol-functionalized polymers. Due to their experimental viability, grafting-to modification reactions have been among the most widely used polymer-modification techniques, for example, to achieve compatibilization of inorganic particles to organic embedding media (Ojha et al 2013). Major advantages of the grafting-to functionalization process involve the wide range of possible polymer chemistries as well as the ability to control chain architectures such as linear, comb, or star (as long as a proper end-functionality allows for tethering of the chain to the surface), as well as the scalability and possibility of continuous processing.…”
Section: Synthesis Of Polymer-tethered (Nano) Particle Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach assumes the same reactivity of both molecules; therefore simply by controlling their ratio in the reaction mixture one can control the concentration of active species on the modified surface [27,38,39]. Unfortunately, in a case of any difference in the reactivity of real and "dummy" initiators, different composition on the surface when compared to the modifying mixture will be generated [40].…”
Section: Introductionmentioning
confidence: 99%